2018
DOI: 10.18510/hssr.2018.628
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Customer Satisfaction of Online Shopping in Oman – Youth Perspective

Abstract: Purpose: The objective of the study was to analyze the impact of online customer satisfaction through the product quality, application safety, delivery guarantee, and the offers through online shopping. Design/methodology/approach: For this research, the purposive sampling method was used to collect 120 samples through a questionnaire– from those who are performing online shopping in Oman especially the youth. SPSS was used to analyze the collected data. Chi-square analysis, ANOVA and Kolmogorov-Smirnov … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…But previously, several authors focused on the website service quality to examine customer satisfaction (Augustie, 2014;Pawlasova & Klezl, 2017;Zatalini & Pamungkas, 2017). Because the electronic service quality can determine how effectively and efficiently a website can provide facilities in case of buying, selling and delivering goods and services to the online shopping customer (Ghaffari and Ashkiki, 2015).…”
Section: Website Service Quality and Customer Satisfactionmentioning
confidence: 99%
“…But previously, several authors focused on the website service quality to examine customer satisfaction (Augustie, 2014;Pawlasova & Klezl, 2017;Zatalini & Pamungkas, 2017). Because the electronic service quality can determine how effectively and efficiently a website can provide facilities in case of buying, selling and delivering goods and services to the online shopping customer (Ghaffari and Ashkiki, 2015).…”
Section: Website Service Quality and Customer Satisfactionmentioning
confidence: 99%
“…A contrast finding was highlighted by Hemalatha and Balakrishnan [25] that addressed the main concern of Indian customers towards online shopping the delay in delivery. Al-Jahwari et al [9] confirmed the role of delivery guarantee in generating online customer satisfaction among young customers in Oman. Thus, the third hypothesis is proposed as below:…”
Section: Slow Delivery Processmentioning
confidence: 95%
“…Al-Jahwari et al [9] conducted a research about factors influencing customer satisfaction in online shopping. They identified that application safety which was measured by safe payment method and personal information protection had significant and positive effect on online customer satisfaction.…”
Section: A Payment Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies 5,69‐79 have examined the factors that significantly influence customer satisfaction and customer loyalty in e‐commerce business. Several factors such as perceived usefulness, perceived ease of use, customer risk perception, customer support, customer trust, promotion, information quality, transaction security, website design, and brand image of e‐commerce influence satisfaction when shopping on an e‐commerce website and has significant impact on customer loyalty.…”
Section: Background and Related Workmentioning
confidence: 99%